EFEKTIVITAS SOSIALISASI PROGRAM JAMINAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP RUMAH TANGGA USAHA PERTANIAN NON PBI DI KABUPATEN JEMBER TAHUN 2015 - Abu Khoiri (Universitas Jember, 2015)
Jember as a regional center for agriculture and plantations in East Java has a population with considerable professional farmers. Health insurance for farmers is indispensable as by the implementation of a national health insurance program as of 1 January 2014. The problem that arises was that the number of informal sector workers (including farmers not PBI) which register was still very little. Therefore, it was necessary to study on the effectiveness of the program socialization JKN on knowledge and attitudes of family farmers. This type of research wasa descriptive observational where researchers conducted interviews and questionnaires as well as performing measurements on several variables being studied without the intervention of the research object. This study was conducted in three (3) districts which have a number of farming households highest in Jember, in August 2015. The variables in the research was the respondents' knowledge, attitude, and information source.The results showed that only 40 respondents (45.4%) had knowledge of the health insurance program. Of the 40 respondents, only 20% were aware of how the mechanism of registration, 22.5% know the mechanism of payment, and 20% know how to take advantage of health services in the health insurance program. Sources of information that most (52.5%) are in the vicinity (word of mouth). The attitude of the majority of respondents rejected the health insurance program participants (68.9%).the socialization of the health insurance program as part of a policy of running less effective communication, especially in the aspect of the transmission, clarity, and consistency. Keywords: socialization, participation, health insurance.